2015
DOI: 10.1523/jneurosci.0049-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Slow Spatial Recruitment of Neocortex during Secondarily Generalized Seizures and Its Relation to Surgical Outcome

Abstract: Understanding the spatiotemporal dynamics of brain activity is crucial for inferring the underlying synaptic and nonsynaptic mechanisms of brain dysfunction. Focal seizures with secondary generalization are traditionally considered to begin in a limited spatial region and spread to connected areas, which can include both pathological and normal brain tissue. The mechanisms underlying this spread are important to our understanding of seizures and to improve therapies for surgical intervention. Here we study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 83 publications
10
42
0
Order By: Relevance
“…This finding aligns with recent work by Martinet et al (29), who mapped the spatiotemporal propagation of neocortical seizures and demonstrated that more consistent and organized ictal recruitment patterns were associated with improved surgical outcomes. Critically, these authors relied on a similar application of the Moran Index to analyze ictal recruitment latency maps, maximizing the comparability of the findings.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding aligns with recent work by Martinet et al (29), who mapped the spatiotemporal propagation of neocortical seizures and demonstrated that more consistent and organized ictal recruitment patterns were associated with improved surgical outcomes. Critically, these authors relied on a similar application of the Moran Index to analyze ictal recruitment latency maps, maximizing the comparability of the findings.…”
Section: Discussionsupporting
confidence: 91%
“…An illustration of the Moran Index applied to various spatial maps is provided in Figure 5 using simulated data. As the simulation demonstrates the Moran Index ranges from −1 (perfect anti-autocorrelation between neighboring channels) to +1 (perfect autocorrelation between neighboring channels), with 0 indicating no pattern of spatial autocorrelation (29). …”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations